Government Size dan Pertumbuhan Ekonomi di Indonesia - Santika, Ary Ratna; Qibthiyyah, Riatu M. (UI Scholars Hub, 2020)
The aim of this research to investigate the effect of government size on regional economic growth in Indonesia. This study uses panel data analysis with using two years of interval data from 2009 until 2015. The results showed that government size has a significant effect on economic growth and it has a non-linear relationship. According the estimation from the model, the threshold government size on regional economic growth is 38.98 percent. Above the threshold, an increase in government size will instead have a negative effect on economic growth.